1994
DOI: 10.5935/0305-7518.19940017
|View full text |Cite
|
Sign up to set email alerts
|

Effective vaccination of mice againstMycobacterium lepraewith density-gradient subfractions of solubleM. lepraeproteins: clues to effective protein epitopes

Abstract: It had previously been discovered that intradermal mouse vaccina tion with a protein fraction of My cobacterium leprae (called soluble proteins) in Freund's incomplete adjuvant (FIA) resulted in consistent and long-lived protection against M. leprae multiplication from subsequent viable fo otpad challenges. In this study certain density-gradient subfractions of this soluble protein, but not others, in FIA afforded vaccine protection. The results of this study suggest which M. leprae proteins may be involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The 10kDa, 65kDa-1 and 28kDa SodA proteins were shown to induce some, albeit limited, protection, whereas the 18 kDa and 35 kDa proteins failed to do so (Gelber et aL, 1994). As indicated above, while some antigens may have a better intrinsic protective potential than others, subunit vaccines may not trigger an immune response that results in a long-term high degree of protection.…”
Section: In Vivo Immunological Protectionmentioning
confidence: 98%
“…The 10kDa, 65kDa-1 and 28kDa SodA proteins were shown to induce some, albeit limited, protection, whereas the 18 kDa and 35 kDa proteins failed to do so (Gelber et aL, 1994). As indicated above, while some antigens may have a better intrinsic protective potential than others, subunit vaccines may not trigger an immune response that results in a long-term high degree of protection.…”
Section: In Vivo Immunological Protectionmentioning
confidence: 98%
“…This has impaired the ability to produce antigens for research purposes, and until recently, studies of antigen-specific immune responses during the course of the disease have been limited to using crude bacterial extracts or a few single M. leprae antigens purified from animal extracts (10,18,27). Partial vaccination against M. leprae can be achieved with other mycobacteria, but a defined subunit vaccine for leprosy is lacking (7,14).…”
mentioning
confidence: 99%
“…Thus, the identification and synthesis of these low-molecular-weight peptides should be pursued. Furthermore, in our previous studies (6)(7)(8), it was found frequently that mouse vaccination with largely proteinaceous subunits of M. leprae provided impressive protection, often with no M. leprae at all being detected in vaccinated mice upon footpad harvests following a preceding viable-M. leprae challenge. Particularly, in a previous study (8), mouse vaccination with soluble proteins of M. leprae resulted in both impressive protection and generally detection of absolutely no acid-fast bacilli at al.…”
Section: Discussionmentioning
confidence: 92%
“…In several studies, mycobacterial growth was also determined 3 months after peak multiplication was noted in the negative control, the plateau phase. It is noteworthy that in studies such as these, there is considerable (10-fold or more) variability in the number of M leprae organisms enumerated at the peak of multiplication in individual footpads of mice immunized with FIA alone (6)(7)(8)27). This is a function of several factors.…”
Section: Materuils and Methodsmentioning
confidence: 99%